Visualizing K48 Ubiquitination during Presynaptic Formation By Ubiquitination-Induced Fluorescence Complementation (UiFC) - Pinto, Maria J.; Pedro, Joana R.; Costa, Rui O.; Almeida, Ramiro D. (Frontiers in Molecular Neuroscience, 2016)
In recent years, signaling through ubiquitin has been shown to be of great importance for normal brain development. Indeed, fluctuations in ubiquitin levels and spontaneous mutations in (de)ubiquitination enzymes greatly perturb synapse formation and neuronal transmission. In the brain, expression of lysine (K) 48-linked ubiquitin chains is higher at a developmental stage coincident with synaptogenesis. Nevertheless, no studies have so far delved into the involvement of this type of polyubiquitin chains in synapse formation. We have recently proposed a role for polyubiquitinated conjugates as triggering signals for presynaptic assembly. Herein, we aimed at characterizing the axonal distribution of K48 polyubiquitin and its dynamics throughout the course of presynaptic formation. To accomplish so, we used an ubiquitination-induced fluorescence complementation (UiFC) strategy for the visualization of K48 polyubiquitin in live hippocampal neurons. We first validated its use in neurons by analyzing changing levels of polyubiquitin. UiFC signal is diffusely distributed with distinct aggregates in somas, dendrites and axons, which perfectly colocalize with staining for a K48-specific antibody. Axonal UiFC aggregates are relatively stable and new aggregates are formed as an axon grows. Approximately 65% of UiFC aggregates colocalize with synaptic vesicle clusters and they preferentially appear in the axonal domains of axo-somatodendritic synapses when compared to isolated axons. We then evaluated axonal accumulation of K48 ubiquitinated signals in bead-induced synapses. We observed rapid accumulation of UiFC signal and endogenous K48 ubiquitin at the sites of newly formed presynapses. Lastly, we show by means of a microfluidic platform, for the isolation of axons, that presynaptic clustering on beads is dependent on E1-mediated ubiquitination at the axonal level. Altogether, these results indicate that enrichment of K48 polyubiquitin at the site of nascent presynaptic terminals is an important axon-intrinsic event for presynaptic differentiation.